2022
DOI: 10.1111/jace.18463
|View full text |Cite
|
Sign up to set email alerts
|

High Na+ conducting Na3Zr2Si2PO12/Na2Si2O5 composites as solid electrolytes for Na+ batteries

Abstract: Sodium superionic conductor Na3Zr2Si2PO12 (NZSP) is a promising material as a solid electrolyte for sodium‐ion batteries. The highest conductivity of ∼1.0 mS/cm at room temperature (RT) was reported for the compound with a Na content of approximately 3.3 per formula unit (f. u.) and when the material is synthesized with a final sintering temperature ≥1220°C. Herein, we propose a new synthesis method to enhance the conductivity of the NZSP by liquid‐phase sintering with the optimum amount of additive of amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Impedance spectroscopy is a well-established technique to determine the conductivity of a material as a function of temperature and frequency. It allows differentiating between the real and imaginary parts of the various electrical parameters, such as impedance, ac conductivity, dielectric constant, electric modulus, and polarizability, which are useful for understanding the electric behavior of a material. This technique provides separate information for grain and grain boundary contributions to ionic conduction.…”
Section: Resultsmentioning
confidence: 99%
“…Impedance spectroscopy is a well-established technique to determine the conductivity of a material as a function of temperature and frequency. It allows differentiating between the real and imaginary parts of the various electrical parameters, such as impedance, ac conductivity, dielectric constant, electric modulus, and polarizability, which are useful for understanding the electric behavior of a material. This technique provides separate information for grain and grain boundary contributions to ionic conduction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the bottlenecks, the higher intersite distances for Na ions lead to higher activation energy and lower ionic conductivity in NCGO as compared to that for KCGO. Such bottlenecks are responsible for the low ionic conductivity as found to be ∼1.6 × 10 –5 S m –1 and 4.6 × 10 –7 S m –1 for KCGO and NCGO, respectively, at 573 K. These values are substantially lower than that of the NASICON compounds. For the NASICON compounds, ionic conduction occurs in 3D without having any bottleneck along the conduction pathways as compared to 2D and 1D in KCGO and NCGO, respectively. Moreover, the partially occupied Na-ion sites are favorable for ionic conductions.…”
Section: Discussionmentioning
confidence: 96%
“…In the recent past, various sodium and potassium-based compounds were synthesized and characterized for ionic conduction investigations. For example, compounds such as A 6 [Rh 4 Zn 4 O­( l -cysteinate) 12 ]· n H 2 O with high conductivity values of ∼5.0 × 10 –2 and ∼1.3 S m –1 at 300 K for A = Na + and K + , respectively; Na 2 Ni 2 TeO 6 with ∼10.1 S m –1 at 573 K, Na 2 Zn 2 TeO 6 with ∼5.1 S m –1 at 573 K, Na 2 Co 2 TeO 6 with ∼3.1 S m –1 at 573 K, and sodium superionic conductor (NASICON) Na 10.8 Sn 1.9 PS 11.8 with 0.67 S m –1 at 298 K were reported recently. These studies revealed that Na + and K + ion based inorganic compounds could be possible candidates for the development of the new ionic conductors.…”
Section: Introductionmentioning
confidence: 99%